Acordos no domínio da improbidade administrativa - Lane, Renata (2020)
The current work aims to analyse consensualness in the field of administrative improbity, examining the viability of agreements encompassing administrative improbity acts and in which arrangements those agreements are possible. Therefore, the study covers the civil microsystem of the administrative probity jurisdiction, the constitutional grounds for protection of administrative probity and the accountability system for administrative improbity acts. The dissertation analyses the possibility of consensus as an alternative route to the more traditional methods of conflict resolution, and then analyses consensualness within Administrative Law and its impact in the authoritative and unilateral acts of administration. Considering the latest changes in the national legal system that allows consensualness as an alternative to resolve administrative improbity, the work addresses how sanctions are no longer the only response of the legal system for administrative improbity acts, aligning agreements with public interest. This new approach culminated with the revocation of the previous ban on the celebration of agreements outlined in §1º, article17 of Law nº 8.429/92. Thus, considering the evolution of the legislation in the field of the administrative improbity, the study assesses which types of agreements are compatible with the new wording of §1º and §10-A, article 17 of Law nº 8.429/1992, amended by Law nº 13.964/2019 (Pacote Anticrime). The work also analyses the validity of agreements celebrated under previous wording of Law nº 8.429/92 as well as the contents and scope of the new wording of the law. Finally, the work examines the types of viable agreements within the field of administrative improbity